Implementation of Human Resources Information System in Employee Recruitment and Career Development Activities - Sharon Ravenska Puimera; Yustina Ertie Pravitasmara Dewi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Technological developments and business competition require companies to be able to compete. Employees must be appropriately managed as one of the company's assets. Therefore the company needs a human resource information system. Human resource information systems help work to be more efficient and effective. This study aims to determine the implementation of human resource information systems in employee recruitment and career development of employees at PT Bahtera Wiraniaga Internusa. The research method uses a qualitative approach and the type of descriptive research. The human resource information system becomes a database for recruitment activities and a tool for evaluating employee performance in employee career development activities.